When There Is No Conversion: Spiritualists and Personal Religious Change - Meintel, Deirdre (Anthropologica, 2022)
This analysis is based on field research on Spiritualists in a Montreal congregation. For most religions that are part of the contemporary scene, conversion marks a transformation of religious identity and is symbolized by special rituals. Although Spiritualism was born in the modern era, conversion is not evident among the spiritualists in the study, and still less, proselytization. I will discuss how Spiritualists experience personal religious change and what light this can shed on more typical changes of religious identity like conversion.